Hyperintensity of Cerebrospinal Fluid on T2-Weighted Fluid-Attenuated Inversion Recovery Magnetic Resonance Imaging Caused by High Inspired Oxygen Fraction - Moioli, Melania; Levionnois, Olivier; Stein, Veronika M.; Schüpbach, Gertraud; Schmidhalter, Marta; Schweizer-Gorgas, Daniela (Frontiers in Veterinary Science, 2017)
In veterinary medicine, patients undergo magnetic resonance imaging (MRI) under general anesthesia to enable acquisition of artifact-free images. The fraction of inspired oxygen (FiO2) ranges between 30 to 95%. In humans, a high FiO2 is associated with incomplete signal suppression of peripheral cerebrospinal fluid (CSF) spaces on T2-weighted fluid-attenuated inversion recovery (T2w-FLAIR) sequences. The influence of FiO2 on T2w-FLAIR images remains unreported in small animals. The aim of this prospective study was to investigate whether a high FiO2 is associated with hyperintensity in peripheral CSF spaces on T2w-FLAIR images in dogs and cats. Client-owned patients undergoing brain MRI were prospectively enrolled. Animals with brain parenchymal abnormalities and/or meningeal contrast enhancement on MRI images and/or abnormal CSF analysis were excluded. Consequently, twelve patients were enrolled. Anesthesia was maintained by isoflurane 0.5-1 minimal alveolar concentration in 30% oxygen. After acquisition of transverse and dorsal T2w-FLAIR images, the FiO2 was increased to 95%. The T2w-FLAIR sequences were then repeated after 40 minutes. Arterial blood gas analysis was performed in six patients at the same time as T2w-FLAIR sequences acquisition. Plot profiles of the SI from CSF spaces of three cerebral sulci and adjacent gray and white matter were generated. Signal intensity (SI) ratios of CSF space and white matter were compared between the T2w-FLAIR images with 30% and 95% FiO2. An observer blinded to the FiO2, subjectively evaluated the SI of peripheral CSF spaces on FLAIR images as high or low. There was significant difference in the partial pressure of oxygen between the two arterial samples (P<0.001). The SI ratios obtained from the T2w-FLAIR images with 95% FiO2 were significantly higher compared with those obtained from the T2w-FLAIR images with 30% FiO2 (P<0.05). The peripheral CSF spaces were subjectively considered hyperintense in 11 of 12 cases on T2w-FLAIR images with 95% FiO2 (P<0.005). A clear difference in SI, dependent on the FiO2 was seen in the peripheral CSF spaces on T2w-FLAIR images. In conclusion, the influence of FiO2 must be considered when differentiating pathological and normal CSF spaces on T2w-FLAIR images in dogs and cats.